Artificial intelligence and the future of endoscopy. Issue 4 (10th April 2019) - Neumann, Helmut; Bisschops, Raf
Abstract : This Editorial refers to the article by S.‐e. Kudo et al., p 363–371 and Y. Mori et al., p 378–388 of this issue.